Charisma, Magic, and Spirituality as Socially Engaged Processes: Lucian’s (circa 120-200) “Alexander the False Prophet” and People’s Accounts of the Supernatural - Prus, Robert (Qualitative Sociology Review, 2017)
Focusing on Alexander the False Prophet and The Lover of Lies, two texts from the Greek poet-philosopher Lucian of Samosata (circa 120-200) of the Classical Roman era, this paper considers (a) charisma, magic, and spirituality as aspects of an interconnected, collectively achieved, developmental process associated with the emergence of a religious cult. Somewhat relatedly, this paper also acknowledges (b) people’s broader, longstanding fascinations with matters that seem incredulous. Depicting a more sustained realm of prophetic activity and an account of people’s intrigues with the supernatural, Lucian’s texts offer some especially valuable transhistorical and transcultural reference points for the broader sociological study of human knowing and acting. The paper concludes with a consideration of the implications of these matters for the study of people’s involvements in religion and spirituality as humanly-engaged realms of endeavor and interchange.